Empowerment Through Feminist Self-Defense: The IMPACT Lasts - Thompson, Martha E. (Violence against women, 2023)
What do women learn in feminist self-defense that is empowering? This study examined the skills women used months and years after completing an IMPACT self-defense course. Ninety-seven survey participants described skills they had used and incorporated into their lives. The major themes that emerged through a classic grounded theory analysis were awareness, boundary setting, assertive body language, and managing adrenaline to prevent, interrupt, or stop uncomfortable, intrusive, or hostile behaviors. IMPACT-trained women did not engage in self-blaming or risky behavior and used their skills to prevent and interrupt aggressive behavior.